Dinamika Interaksi Pustakawan dan Pemustaka di Era Kecerdasan Buatan - Hirjani, Baiq Asshaela; Safii, Moh. (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to analyze the dynamics of librarian and user interaction in the era of artificial intelligence. The method used is qualitative with the Systematic Literature Review (SLR) approach. The results of the study show that AI drives the transformation of library services to be more automatic, faster, and more personal. Although this technology increases efficiency, concerns arise regarding data privacy and the professional role of librarians. However, librarians are still needed as knowledge facilitators, information literacy educators, and technology ethics directors. Meanwhile, users show interest in AI-based services, but want security and transparency guarantees. Thus, the success of AI integration in libraries depends on the competence of librarians, digital literacy of users, and ongoing policy support and collaboration.